Perencanaan lansekap ekowisata pesisir di Desa Beraban, Kecamatan Kediri, Kabupaten Tabanan - Fitriana, Devvy Alvionita; Yusiana, Lury Sevita; Gunadi, I Gusti Alit (Jurnal Arsitektur Lansekap; Vol.4, No.1, April 2018, 2018)
Coastal ecotourism landscape planning in Beraban Village, Kediri District, Tabanan Regency. Beraban Village is one of the villages in the district of Kediri, Tabanan Regency which has potential as a coastal ecotourism area. Coastal ecotourism is a tourism activity that is responsible for the welfare of local communities and the preservation of coastal environments. This research is focused on Nyanyi Beach area because there are coastal forest ecosystem with pes-caprae formation and barringtonia formation whose existence requires conservation. This study aims to determine the problems and potential of Beraban Village as a reference in coastal ecotourism landscape planning. The method used in this research is the method of ecotourism planning according to Fennel (2003). The concept of coastal ecotourism landscape planning selected is coastal ecotourism that educates coastal ecosystems and protects coastal forest ecosystems. The result of planning coastal ecotourism was applied to the spatial plan (entrance area, core tourism area, buffer area and conservation area), plans of activity and facility.